PRINSIP–PRINSIP KESOPANAN DALAM FILM HOME ALONE KARYA JOHN HUGHES ( SUATU ANALISIS PRAGMATIK ) - Siwu, Naftali Ester; Lasut, Theresia M.C; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
ABSTRACT                                                Naftali Ester Siwu1                                     Dra.Theresia M. C. Lasut, M.Hum2                                   Dr. Garryn Ch Ranuntu, S,pd, M.Hum3     This study is entitled Prinsip-prinsip Kesopanan dalam Film Home Alone. The aims of this study are to identify, clasify, and analyze the maxims that related to politeness principles and their functions found in the Film Home Alone. The method of this study is descriptive method. The technic of this study are collecting, classifying and anaykzing data. The data were collected through conversation among the characters. This study using Leech’S (1983) theory. The result shows that there are six maxim of politeness principles and their function. Those are tact maxims, genorisity maxim, approbation maxim, modesty maxim, aggrement maxim, and sympathy maxim. It is expected that this research will help students and readers in learning pragmatisc, especially on politeness principles.- - - - - - - - - - - - - - - - - - - - - - - - - -Keywords: Pragmatic, Politeness, film: Home Alone